2014
DOI: 10.1007/s00421-013-2804-7
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability during exertional heat stress: effects of heat production and treatment

Abstract: While EHS has a marked effect on autonomic nervous system modulation and whole-body immersion in 2 °C water results in faster cooling, there were no observed differences in restoration of autonomic heart rate modulation as measured by HRV indices with whole-body cold-water immersion compared to passive recovery in thermoneutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…() following 2 °C CWI (35.7 °C). Thus, we confirm the previous recommendations (Proulx et al., ; Gagnon et al., ; Flouris et al., ) that a similar exit temperature should be used even if cooling of the exertional heatstroke victim is delayed by as much as 40 min.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…() following 2 °C CWI (35.7 °C). Thus, we confirm the previous recommendations (Proulx et al., ; Gagnon et al., ; Flouris et al., ) that a similar exit temperature should be used even if cooling of the exertional heatstroke victim is delayed by as much as 40 min.…”
Section: Discussionsupporting
confidence: 91%
“…It is well accepted that immediate treatment with CWI is the gold standard for EHS and exertional heatstroke (Casa et al., , ; Flouris et al., ). In this study, we examined the effectiveness of CWI (core cooling rates during immersion and core temperature afterdrop following immersion) for treating EHS when delays of 5, 20, and 40 min are present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy young adults, Flouris et al [5] found that marked exercise-induced hyperthermia (i.e., core body temperature C39.5°C) had a significant effect on ANS control as assessed by HRV which was restored only when core body temperature returned to pre-exercise baseline resting levels. Whether or not this pattern of response is exacerbated in individuals with T1DM or occurs at a lower level of heat stress remains to be elucidated.…”
mentioning
confidence: 99%